2020
DOI: 10.1186/s12914-020-00234-y
|View full text |Cite
|
Sign up to set email alerts
|

A social-ecological examination into the research, policy and health service delivery environment related to early marriage and sexual and gender-based violence among youth in Jordan

Abstract: Background: The determinants of sexual-and gender-based violence (SGBV) and early marriage are embedded across different levels of the social ecological system, including at the individual, family, community, and policy levels. In Jordan and the Middle East, SGBV, honor killing, and early marriage are priority public health and human rights issues that often overlap, and affect a significant percentage of youth. Jordan is home to a large number of refugees from across the Middle East, who may be even more vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…Several participants in our study also described that many families are resorting to marriages outside of the Syrian community and, in particular, men from other wealthier countries to expand their family's supportive network and the social, institutional, and financial resources available to them. This finding was consistent with previous studies [17,22,23]. At the same time, however, our results show that living in host communities has a positive influence and offers some parents and girls the opportunity to question social expectations and social norms and to ultimately, openly refuse or reject CM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Several participants in our study also described that many families are resorting to marriages outside of the Syrian community and, in particular, men from other wealthier countries to expand their family's supportive network and the social, institutional, and financial resources available to them. This finding was consistent with previous studies [17,22,23]. At the same time, however, our results show that living in host communities has a positive influence and offers some parents and girls the opportunity to question social expectations and social norms and to ultimately, openly refuse or reject CM.…”
Section: Discussionsupporting
confidence: 93%
“…Although the shifts in social norms enabled some participants in this study to exercise agency in decisions related to their marriage are encouraging and may indeed represent an opportunity for intervention, the discussion about agency in this setting may be far more complicated. In a setting where girls may be subject to extreme consequences, including honor killing, for even minor transgressions against what is socially acceptable [17], efforts to improve girls' agency must be carefully implemented and conducted in tandem with efforts to change the overarching harmful social norms that limit their agency. Gender norms that limit girls' participation must also change along with those that relate to marriage, to enable girls and young women to exercise full agency in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing ever-married women may limit generalizability. Still, in a conservative society, like Jordan, marriage outside wedlock is punishable by law and puts women at risk of honor killing [ 65 , 66 ]. This may eliminate the generalizability limitation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Girls who marry before the age of 18 are more likely to experience violence, especially when the spousal age gap is large (Clark et al 2017;Al-Modallal 2012). Another study found that girls who were married before 18 were twice as likely to report domestic violence and also showed signs of severe depression (Gausman et al 2020). In the Gaza Strip, 63% of early-married girls were exposed to at least one type of violence, compared with 51% of older women (PCBS 2019b).…”
Section: Consequences Of Child Marriagementioning
confidence: 99%